Alkaloid Synthesis via Gold‐Catalyzed Carbon‐Carbon Bond Formation Using Enamine‐type Nucleophile. Issue 5 (30th March 2018) - Wang, Shaozhong
Abstract: In this account, various types of cyclizations/cycloisomerizations of alkyne substrates with internal enamine‐type nucleophiles including enamide, enaminone, enaminoester and in situ generated enamine in the presence of electrophilc transition metal catalysts (Pt, Rh, Cu, Au) are firstly introduced. Then, the applications of the gold‐catalyzed reactions in the synthesis of an array of alkaloids are discussed. These natural products feature heterocyclic structural motifs such as pyridine, azaanthraquinone, pyridoacridine, pyrrole, indole, indolenine and carbazole, as well as chiral tetrahydroindolizine, azocine units and six‐membered carbocycles bearing a quaternary carbon center. Abstract :